Artists Excel on Image Activation But Not Image Manipulation Tasks. (January 2021) - Drake, Jennifer E.; Simmons, Seymour; Rouser, Seth; Poloes, Isabella; Winner, Ellen
The ability to envision what is not directly seen is important in the visual arts, since artists do more than reproduce what they see. Such envisioning requires visual imagery abilities. In this study, we examined whether art students ( n = 32) have enhanced visual imagery abilities compared to nonart students ( n = 40). We administered four tasks designed to assess visual imagery. Three tasks assessed the ability to activate mental images: vividness of visual imagery, recognition of out-of-focus pictures, and abstraction; the fourth task assessed the ability to manipulate mental images: mental rotation. We also administered a verbal IQ and a creativity test to determine whether these measures should be included as covariates in our analyses. Results showed that art students excelled on two of the three image activation tasks, vividness of visual imagery and abstraction, but did not excel on the image manipulation task of mental rotation.